2006
DOI: 10.1080/00103620500408829
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Uptake of Maize Affected by Nitrogen and Potassium Fertility in a Humid Subtropical Environment

Abstract: Nitrogen (N) and potassium (K) fertility management of maize (Zea mays L.) in the humid subtropical Mississippi Delta may differ from a temperate climate because of its use in rotation with cotton (Gossypium hirsutum L.), soil temperatures rarely falling to 08C, and heavy winter rains that facilitate nutrient losses. An experiment to determine the [N] (concentration ¼ [ ]), phosphorus [P], [K], calcium [Ca], magnesium [Mg], iron [Fe], manganese [Mn], zinc [Zn], and copper [Cu] and their total contents plant 21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 10 publications
5
37
1
1
Order By: Relevance
“…The results of Bruns and Ebelhar (2006) similarly demonstrate that K fertilization does not affect the concentration of P in the maize organs.…”
Section: Resultssupporting
confidence: 66%
“…The results of Bruns and Ebelhar (2006) similarly demonstrate that K fertilization does not affect the concentration of P in the maize organs.…”
Section: Resultssupporting
confidence: 66%
“…In a previous study, N application increased the maize grain Mn concentration [10]. Another study showed that increasing the N supply significantly improved yield, but it had little effect on maize grain Zn concentration [12].…”
Section: Grain Micronutrient 'Dilution' May Not Be Caused By Higher Gmentioning
confidence: 99%
“…Application of N fertilizer increased the concentration of Mn in the grain, but the higher grain yield resulting from N fertilization resulted in a grain Zn 'dilution' effect [10]. Increasing N supply significantly improved the yield but had little effect on the grain Zn concentration in maize [12]. In addition, modern maize varieties with higher yields tend to contain lower concentrations of micronutrients in the grain, compared with those in grain of the lower-yield conventional varieties [10].…”
mentioning
confidence: 99%
“…The increase of NUE is consequence of enhanced uptake and improved utilization by the crop. However, yield response to potassium fertilization depends to a great extent on the level of nitrogen supply (Bruns and Ebelhar 2006, Brennan and Bolland 2007, 2009). …”
Section: Resultsmentioning
confidence: 99%